การศึกษาการดําเนินงานประกันคุณภาพการศึกษา ของสถาบันการพลศึกษา วิทยาเขตเพชรบูรณ์ ประจำปีการศึกษา 2555 - Sukdee, Siriwan; Sitthichanda, Sunti; Punyaping, Poonyanuch; Pumpipith, Lawan (Academic Journal of Thailand National Sports University, 2022)
The purpose of this research was to study and compare Education Quality Assurance Implementations at Physical Education Institutes of Petchaboon During 2013Acadamic Year The subject of 52 were Stratified Random Sampling from of administrator, nd serviceman at Physical Education Institutes of Petchaboon During 2013Acadamic Year. The data were collected by the researcher’s constructed questionnaire (r = .90) and treated for mean, standard deviation, one-way ANOVA and testing for pair differences by LSD (Least Significant Difference). The results were as follows 1) The quality assurance implementations at Physical Education Institutes of Petchaboon During 2013-Acadamic Year as a whole and individual 4 aspects were high level. 2) When comparing the quality assurance implementations at Physical Education Institutes of Petchaboon During 2013-Acadamic Year as perceived between administrator, lecturer, and serviceman were significantly different at the level of .05. 3) When comparing the quality assurance implementations at Physical Education Institutes of Petchaboon During 2013-Acadamic Year administrator as perceived by staff Members with different work experience were no significantly different. 4) When comparing the quality assurance implementations at Physical Education Institutes of Petchaboon During 2013-Acadamic Year administrator as perceived by staff members in different working faculties.